Eliminating Leakage Current in Thin‐Film Transistor of Solution‐Processed Organic Material Stack for Large‐Scale Low‐Power Integration. (27th April 2022) - Han, Lei; Li, Jun; Ogier, Simon; Liu, Zhe; Deng, Li'ang; Cao, Yu; Shan, Tong; Sharkey, Dan; Feng, Linrun; Guo, Aiying; Li, Xifeng; Zhang, Jianhua; et al.
Abstract: For organic thin‐film transistors (OTFTs) made of solution processed stacks of organic semiconductor and dielectric materials, it is a grand challenge to eliminate the leakage current paths. With a top‐gate bottom‐contact structure, this work introduces a strong dipole interfacial layer made of self‐assembled monolayer (SAM) molecules at metal‐semiconductor contacts to suppress minority carrier injection for low leakage and stable operation, while not affecting majority carrier injection. Both gate insulator (GI) leakage and parasitic leakage in the device architecture are also effectively suppressed with a sputtering‐resistant polymer GI layer and photolith patterned OSC islands, respectively. The devices present a decent mobility with a typical value of 1.98 cm 2  V –1  s –1, record‐low leakage current at 10 –18  A µm −1 and large ON/OFF ratio (>10 10 ) in a wide gate voltage range (100 V), reaching the theoretical limit and also the best level of inorganic counterparts despite much lower processing temperature (120 °C). Manufacturability of the material stack is verified on a 200 mm × 200 mm substrate and the fabricated 4.7 in. active‐matrix organic light‐emitting diode display, integrating more than 150 000 OTFTs, can be operated at ultra‐low frame‐rate (0.1 Hz) for power saving. Abstract : This work addresses the challenge of eliminating the leakage current paths in solution processed organic thin‐film transistors (OTFTs) for large‐scale low‐power integration. The device presents record‐low OFF‐state leakage, large ON/OFF ratio, and excellent operational stability. The built active‐matrix organic light‐emitting diode display, integrating more than 150k OTFTs, can be operated at ultra‐low frame‐rate (0.1 Hz).